Effective Factors on Faculty Members Job Satisfaction in Mazandaran University of Medical Sciences School of Medicine 2006 - Mansour Ranjbar; Kourosh Vahidshahi (Kerman University of Medical Sciences, 2008)
Background & Objective : Faculty members are one of the most important parts of Input in the Educational system so fine determination of effective factors on their Job satisfaction is critically important This study was designed to evaluate effective factors on faculty members job satisfaction in Mazandaran University of Medical sciences 2006 Methods : In this descriptive cross sectional study all faculty members (135 ones) of medical college who participated as the study samples completed a questionnaire (based on Herzberg theory) consisted demographic variables 40 items in 11 domains for assessment of effective factors on job satisfaction according to 4 point Likert seal degree Results : Among our sample 106 faculty members participated in the study (875% response rate) majority of them were clinical specialists and sub specialists and mostly were assistant professors (735%) The highest mean score (±SD) for effective domains on job satisfaction were as follow: salary 381(±061) condition of work environment 372(±075) job position 33(±081) The least important domains include: method of monitoring and supervising 191(±063) gratitude 2(±074) and communications 202(±085) Basic sciences faculties cared significantly more about salary steady job environment career promotion and quality while for assistant professors environment and responsibility were more significant Conclusion : This study showed that external factors including salary and job environment were the most effective factors on job satisfaction of faculty members but factors related to organizational position of faculty members (communications and supervision) were less important In Overall this study indicated less importance of organizational and team spirit in faculty members and predominance of individual benefits which should be modified by appropriate programs